2022
DOI: 10.1051/e3sconf/202236101002
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and entrepreneurship behavior of strawberry farmers in Serang Village, Karangreja District, Purbalingga

Abstract: Entrepreneurship is an important mechanism that facilitates the transfer of knowledge and skills that ultimately results in economic growth. Entrepreneurship is needed by strawberry farmers in Serang Village to face future challenges. This research aims to; 1) identify the internal and external entrepreneurial characteristics of strawberry farmers, and 2) analyze the influence of entrepreneurial characteristics on the entrepreneurial behavior of strawberry farmers. Respondents were determined using the census … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…In another study, Puspitasari et al (2022) examined the entrepreneurial behavior of horticultural farmers and found similar traits of them being diligent, responding to opportunities, innovative, risk-taking, and independent. In their research on strawberry farming, Besides, farmers' entrepreneurial behavior was shown by the characteristics of risk-taking, responding to opportunities, innovation, and independence (Wijayanti et al 2022).…”
Section: Entrepreneurialmentioning
confidence: 99%
See 2 more Smart Citations
“…In another study, Puspitasari et al (2022) examined the entrepreneurial behavior of horticultural farmers and found similar traits of them being diligent, responding to opportunities, innovative, risk-taking, and independent. In their research on strawberry farming, Besides, farmers' entrepreneurial behavior was shown by the characteristics of risk-taking, responding to opportunities, innovation, and independence (Wijayanti et al 2022).…”
Section: Entrepreneurialmentioning
confidence: 99%
“…Previous empirical studies emphasize the contribution of entrepreneurial behavior and innovative behavior in an agricultural business (Amir, 2015;Wanyonyi & Bwisa, 2015;Faria & Mixon, 2016;Khoshmaram et al 2020;Li et al 2022;Puspitasari et al 2022;and Wijayanti et al 2022). However, the causality and threshold regression of entrepreneurship and innovative behaviors for millennial farmers are largely ignored.…”
Section: The Econometric Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…Sementara itu, karakteristik eksternal berasal dari lingkungan ekonomi, sosial, fisik dan Selain itu, hasil penelitian juga menunjukkan bahwa karakteristik internal dan eksternal kewirausahaan petani stroberi memiliki pengaruh positif dan signifikan terhadap perilaku kewirausahaan. Hasil penelitian mengidentifikasi bahwa tingkat kesadaran kelembagaan perlu ditingkatkan dalam kerja sama petani stroberi, meskipun petani stroberi bersifat mandiri, namun untuk meningkatkan hasil panen yang maksimal diperlukan pihak-pihak tertentu yang dapat membantu mereka (Wijayanti et al, 2022).…”
Section: Characteristics and Entrepreneurship Behavior Of Strawberry ...unclassified